Cloning and expression of a Pitx homeobox gene from the lamprey, a jawless vertebrate. - Boorman, C; Shimeld, S (2002)
The Pitx homeobox gene family has important roles in vertebrate pituitary, eye, branchial arch, hindlimb and brain development, as well as a key function in regulating left-right asymmetry. Here we report the isolation of a Pitx gene, PitxA, from two lamprey species, Lampetra planeri and Petromyzon marinus. Molecular phylogenetics show PitxA is most closely related to the Pitx1 and Pitx2 genes of jawed vertebrates, however resolution in the trees is insufficient to determine if PitxA is orthologous to a specific jawed vertebrate gene. In situ hybridisation studies show lamprey PitxA is expressed in the developing nasohypohyseal system and stomodeal ectoderm from early development through to early ammocoette larvae. PitxA expression was also detected in several areas of the developing brain, in the developing optic system, in pharyngeal endoderm and endostyle and in the lateral somite. These results show some key aspects of Pitx gene expression in gnathostomes are primitive for all living vertebrates.